2017
DOI: 10.1101/137760
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loss of PTEN promotes formation of signaling-capable clathrin-coated pits

Abstract: Defective endocytosis and vesicular trafficking of signaling receptors has recently emerged as a multifaceted hallmark of malignant cells. Clathrin-coated pits (CCPs), the fundamental unit of clathrin-mediated endocytosis, display highly heterogeneous dynamics on the plasma membrane where they can take from 20 seconds to over a minute to form cytosolic coated-vesicles. Despite the large number of cargo molecules that traffic through CCPs, it is not well understood whether signaling receptors activated in cance… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 63 publications
3
34
0
Order By: Relevance
“…Previous work from our lab have shown that retinal pigment epithelial (RPE) cells spread on large fibronectin islands (to induce high membrane tension), exhibited an increase in proportion of abortive CCSs and smaller CCPs 22,23 . Using SIM-TIRF super-resolution imaging of RPE cells stably expressing mCherry-clathrin light chain (CLC), we characterized the morphology of CCSs and classified them into three categories: (i) Abortive CCSs, which are coated structures which dissemble before they reach maturation [24][25][26] , (ii) Stalled CCSs, which are persistent, noninternalizing coated structures in the imaging field 8,12 , and (iii) Productive CCPs, which are coated structures undergo initiation, assembly, and transition to coated-pits followed by membrane scission and internalization. Lifetime analyses of CCSs have shown that abortive CCSs have a lifetime less than 20 s 27-29 and stalled CCSs have a lifetime above 120 s 8,12,27 .…”
Section: Overexpression Of Epsin In Cells Reduces Abortive Ccss At Himentioning
confidence: 99%
“…Previous work from our lab have shown that retinal pigment epithelial (RPE) cells spread on large fibronectin islands (to induce high membrane tension), exhibited an increase in proportion of abortive CCSs and smaller CCPs 22,23 . Using SIM-TIRF super-resolution imaging of RPE cells stably expressing mCherry-clathrin light chain (CLC), we characterized the morphology of CCSs and classified them into three categories: (i) Abortive CCSs, which are coated structures which dissemble before they reach maturation [24][25][26] , (ii) Stalled CCSs, which are persistent, noninternalizing coated structures in the imaging field 8,12 , and (iii) Productive CCPs, which are coated structures undergo initiation, assembly, and transition to coated-pits followed by membrane scission and internalization. Lifetime analyses of CCSs have shown that abortive CCSs have a lifetime less than 20 s 27-29 and stalled CCSs have a lifetime above 120 s 8,12,27 .…”
Section: Overexpression Of Epsin In Cells Reduces Abortive Ccss At Himentioning
confidence: 99%
“…This has revealed broad heterogeneity of CCPs, including in size, distribution within the cell surface, lifetime and protein composition. 48,70,[76][77][78][79][80][81][82][83][84][85][86] In addition, specific CCP properties have been linked to cargo receptor content. 78,85 This type of data has allowed the construction of computational models to describe CCP assembly and scission, 87 from which now emerges the synergism between predictions made by these computational models and experimental testing that are at the core of systems biology.…”
Section: Heterogeneity Of Molecular Assemblies and Organelles In Mementioning
confidence: 99%
“…Recently, PTEN is also shown to play a role in regulation of CCP dynamics. PTEN regulates the proportion of shortlived CCPs depending on its lipid phosphatase activity (49). According to our study, PTENa is involved in CME regulation by interacting with amphiphysin depending on its protein phosphatase activity.…”
Section: Discussionmentioning
confidence: 60%